THE INFLUENCE OF HUMAN RESOURCE CAPACITY DEVELOPMENT ON LOYALTY AND ITS IMPLICATIONS FOR EMPLOYEE PERFORMANCE - Ading Rahman Sukmara; M Sidik Priadana; Senen Machmud (Jurnal Ekonomi, 2023)
One of the government programs that has become its mainstay is strengthening the economic sector, because with the economy, the Indonesian people will be free from poverty. One of the factors of national competitiveness is the quality and capacity of human resources in our nation's human resources. The economic progress of the Japanese and Singaporeans is mainly supported by the high quality of human resources in the mastery of science and technology which is a competitive advantage even though both of them are poor in natural resources. Efforts to increase Human Resources carried out by the Indonesian government include increasing productivity in various industrial or corporate sectors, both private and government-owned companies. This increase in productivity is in addition to increasing employee competence, motivation, and understanding of employee tasks which affect their performance as output in carrying out their daily activities. Thus, if every employee in various corporate agencies has high performance, a strong state economy will be realized. As mandated by the Government of the Republic of Indonesia through Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies, it states that a national economy based on economic democracy with the principles of togetherness, efficiency with justice, sustainability, environmental awareness, independence, and by maintaining a balance of progress and economic unity national level, needs to be supported by strong economic institutions in the context of realizing people's welfare.